Effect of Different Fluoride Agents on the Load Deflection Characteristics of Heat Activated Nickel Titanium Arch Wires (An in Vitro Study) - Hashim, Rawaa Saadoon; Al-Joubori, Sami K. (Journal of Baghdad College of Dentistry, 2017)
ABSTRACTBackground:Hydrogen absorption and related degradation in the mechanical properties of Ni-Ti based orthodontic wires has been demonstrated following exposure to fluoride prophylactic agents. This study was designed to investigate the effects of three fluoride containing agents on the load deflection characteristics of heat activated nickel titanium arch wires during unloading phase.Material and method: Eighty specimens of heat activated nickel titanium arch wires were obtained from Ortho Technology Company, half of which had a 0.016 inch round and 0.019x0.025 rectangular. Ten specimens from both wire size were immersed in one of the tested fluoride prophylactic agents (neutral sodium fluoride gel, stannous fluoride gel or phos-flur mouth rinse) or in the controlled medium â€œnormal salineâ€, and incubated at 37ËšC for sixty minutes.A Wp 300 universal material testing machine was modified and used to perform a three point bending test in a water path at 37ËšC Â±1ËšC.The statistical difference between the different agents were analyzed using ANOVA and LSD tests.Results: The unloading forces at 0.5, 1.0, and 1.5 mm where significantly reduced especially in neutral sodium fluoride treated specimens.Conclusion: Based on the results founded in th study it might be preferred to use prophylactic agent with the least fluoride ions concentration.It can be concluded that the tested agents have only a limited effect on the load deflection behavior of the heat activated Ni-Ti wires, in a way that they do not have a clinically significant effect on the mechanical behavior of these wires.